Resident physicians in Mexico: tradition or humiliation - Donovan Casas Patiño (Medwave, 2013)
Mexico has a great history and tradition in relation to the training of resident physicians, but what we find behind this process?, Power relations implied and not implied, unnoticed or ignored for convenience by the academic and health institutions, with the aggravation of forgetting its commitment to the training of men and women "professionals" and limited to meet another indicator of "human resources for health." The resident physician in academic and scientific training is immersed in this dehumanized maelstrom and ends up becoming a character for the domain of knowledge as power, forgetting that his act and its rationale lies in the principle of "primum non nocere" to that we would add: nor your person, nor your fellowman, much less whom you have the moral, ethical and civic responsibility to convey some of your knowledge and your experience, that is, part of your essence”.